LEARNING MODEL IN THE DEVELOPMENT OF ISLAMIC CIVILIZATION AT THE STATE OF ISLAMIC RELIGION INSTITUTE OF LHOKSEUMAWE - Hatta, Muhammad (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2021)
ABSTRACTThis study aims to determine the learning model for the development of civilization at IAIN Lhokseumawe. The method of research that is used is to use approach qualitative. This means that the data collected is not in the form of numbers, but the data comes from the results of interviews, field observations, personal documents, memo notes, and other official documents. The research results are Islamic Religious Education in the scope of face-to-face lectures in class for one semester and Islamic Religious Education in activities that are outside the classroom such as seminars scheduled by the department as a form of development of PAI lectures carried out in class.Â Â  There is also an activity that is an advancement for IAIN Lhokseumawe, namely student mobility to Malaysia, which involves PAI students. The learning model in the PAI department at IAIN Lhokseumawe whose learning is based on the Student Center Learning (SCL) is to combine two learning models, namely a learning model that uses a Sufism approach and a learning model that refers to modern learning theories. The learning model with the Sufism approach used is the ta'lim model, the repetition model, the directive model, and others. Meanwhile, the learning model in the PAI department regarding modern theories used includes the cooperative model, the Contextual Teaching Learning (CTL) model, the inquiry model, and various other models.Keywords: Learning Model, Islamic, Civilization